ADAPTATION PATTERN OF MOOCS PLATFORM FOR UPSKILLING AMONG LIS PROFESSIONALS - Upreti, Amruta Nareshchandra; Pal, Asharam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores library and Information Science professional learning behaviour towards MOOCs platform. Data was collected using structured questionnaire analyzing awareness and learning pattern of LIS professionals. The study discusses awareness towards Indian & International platforms. Enrollment of LIS professionals on the MOOC platform for upskilling. International platforms like Alison, Udacity and Coursera had both less awareness and participation among the LIS professionals. The study highlighted challenges related to time management and scheduling conflict, motivation and engagement, technical and infrastructure and adaptation to technology. Findings further revealed that LIS professionals need to engage more in learning through platforms such as MOOCs for career upliftment and professional development.